Investasi Syariah sebagai Strategi Pembangunan Masa Depan yang Berkelanjutan: Kajian Konseptual dan Empiris - Maulana Muklis; Alwi Bisri; Rahmat, Paisal; Hannum, Ummi (Yayasan Literasi Sains Indonesia, 2025)
Sustainable development has become a global priority that requires the integration of economic, social, and environmental goals. Islamic finance, which is based on maqashid sharia and ethical principles, offers a structured framework to align investment practices with the needs of sustainable development. This study examines how Islamic investment principles integrate with the SDGs by evaluating the contribution of Islamic financial instruments in Indonesia and identifying key challenges and opportunities. Using a qualitative descriptive desk research design, data was systematically collected from academic journals, official publications, and policy documents, then analysed through content analysis with source triangulation and peer-review. The findings show that green sukuk issuance has funded five renewable energy and sanitation projects, reduced carbon emissions, and generated risk-adjusted returns comparable to conventional sukuk with better risk management. Productive waqf schemes have channelled public capital into sustainable agriculture and education, improving food security and human capital, and corporate zakat programmes have encouraged the development of MSMEs. Portfolio studies show positive impacts on economic growth and social development, mediated by good governance and regulatory support. Nonetheless, gaps remain in terms of the availability of reporting standardisation, and investor literacy highlighting the need for harmonised frameworks and capacity building. The study concludes that Islamic financial instruments significantly advance sustainable development in Indonesia, and recommends regulatory incentives, standardised Islamic ESG reporting, sustainable thematic funds, and digital financial planning platforms to make the most of Islamic investment potential for a sustainable future.